Transcriptomics of Lactobacillus paracasei: metabolism patterns and cellular responses under high-density culture conditions - Li, Liangzhi; Zhang, Hetian; Meng, Delong; Yin, Huaqun (Frontiers in Bioengineering and Biotechnology, 2023)
Lactobacillus paracasei has significant potential for development and application in the environmental field, particularly in addressing malodor pollution. This study aims to investigate the cellular response of L. paracasei B1 under high-density culture conditions. The selected strain has previously shown effective deodorizing and bacteriostatic abilities. Transcriptomics techniques are employed to dissect the nutrient metabolism pattern of L. paracasei B1 and its response mechanism under environmental stress. The study characterizes the functions of key differentially expressed genes (DEGs) during growth before and after optimizing the culture conditions. The optimization of fermentation culture conditions provides a suitable growth environment for L. paracasei B1, inducing an enhancement of its phosphotransferase system for sugar source uptake and maintaining high levels of glycolysis and pyruvate metabolism. Consequently, the strain is able to grow and multiply rapidly. Under acid stress conditions, glycolysis and pyruvate metabolism are inhibited, and L. paracasei B1 generates additional energy through aerobic respiration to meet the energy demand. The two-component system and quorum sensing (QS) play roles in the response and regulation of L. paracasei B1 to adverse environments.The strain mitigates oxygen stress damage through glutathione metabolism, cysteine